LITERASI MEDIA BERBASIS PENDIDIKAN KARAKTER BAGI MAHASISWA PGSD UNNES - Sukasih, Sri; SB, Nugraheti Sismulyasih; Harmanto, Harmanto (Universitas Negeri Semarang, 2015)
The purpose of this study was to determine the level of understanding of media literacy Unnes PGSD students , particularly on understanding the character -based literacy education and the impact of literacy for students . This study was conducted di PGSD Unnes Semarang in the second half of the school year 2013/2014 on subjects Indonesian Language Skills and compose SD . The results showed an increased understanding of literacy and its impact on students. It can facts with productivity generated by the students during the lectures. Understanding students on media literacy shown by the average scores obtained in the early stages 64 with both categories . The increase in scores occurred after the implementation of the action with an average score of 84 was very good category . The conclusions of this research is the understanding of media literacy can affect the development of the character of the students in the lecture .